2016
DOI: 10.4269/ajtmh.15-0852
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Fatal Serotonin Syndrome–Like Human Rabies Caused by Tricolored Bat–Associated Rabies Virus

Abstract: Abstract. Human rabies is a fatal disease, transmitted by saliva of infected animals, and the diagnosis requires a high index of suspicion. Very few cases are reported annually in the United States. We present a case of human rabies without a clear exposure history that masqueraded as serotonin syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…The language routinely employed included a repertoire of value-laden terms such as "attacked" (Steece & Calisher 1989), "threat" (Wynne et al 2014), and "fatal" (Regunath et al 2016), and passages were loaded with negative connotations prone to misinterpretation. For instance, authors reported that "many zoonotic viruses that have emerged recently are thought to have their origins in bats" (Wang et al 2015) and that "many emerging and re-emerging infectious diseases are zoonoses derived from wildlife, particularly bats" (Wynne et al 2014).…”
Section: Bats Viruses and Framesmentioning
confidence: 99%
“…The language routinely employed included a repertoire of value-laden terms such as "attacked" (Steece & Calisher 1989), "threat" (Wynne et al 2014), and "fatal" (Regunath et al 2016), and passages were loaded with negative connotations prone to misinterpretation. For instance, authors reported that "many zoonotic viruses that have emerged recently are thought to have their origins in bats" (Wang et al 2015) and that "many emerging and re-emerging infectious diseases are zoonoses derived from wildlife, particularly bats" (Wynne et al 2014).…”
Section: Bats Viruses and Framesmentioning
confidence: 99%